Managing Diabetic Nephropathies in Clinical Practice - Bakris, George L.; Hahr, Allison; Khardori, Romesh; Koya, Daisuke; Molitch, Mark; Prischl, Friedrich C.; Schernthaner, Guntram; Thajudeen, Bijin (Springer International Publishing : Imprint: Adis, 2017)
An overview of the diagnosis, treatment, and long-term management of diabetic-related kidney disease in clinical practice. Includes an evidence-based discussion of currently available and experimental drug therapies currently in development, guided by international consensus guidelines. Ideal for physicians, medical trainees, nurses and other medical professional that regularly screen and treat patients with all types of diabetes.- Resumé vydavatel